Evaluación de las funciones de docencia, investigación, vinculación con la colectividad y gestión y su relación con el desarrollo de la escuela de derecho, de la facultad de ciencias sociales, de la UTMACH, periodo lectivo 2012-2013 y propuesta de un plan integral de formación docente. - Franco Barriga, Jenner Javier (2012)
The purpose of this research was to determine the relationship between teaching, research, links with the community and especially management , including leadership and organizational culture in educational institution such as the Technical University of Machala , we worked on a quantitative approach with a series of descriptive methodology especially correlate in the population of principals and teachers of the Technical University of Machala , where sample through a sample extracted by stratified cluster . The results indicate a self-perception and perception of lower middle leader transactional leadership .